Computational fluid dynamics of industrial scale spray dryer - Noor Intan Shafinas, Muhammad (2011)
This thesis presents computational fluid dynamics(CFD) modelling of hydrodynamics in a co-current spray dryer.At first,the grid dependence studies were performed.Various modelling strategies were then studied performed to assess the suitability of the discretisation,solver type and turbulence model.Once the numerical method has been established, further simulations were then performed using three different turbulent models, i.e.standard kε(SKE), Realizable k-ε(RKE)and the Detached Eddy Simulation(DES). Multiphase modelling was performed using discrete phase modelling to model the particle movement inside the drying chamber.The intermediate grid with 420K cells was used for this work in interest to minimise the computational time. Furthermore,the unsteady solver was perform due to the experimental measurement usually taken time averaged quantities which is mimic to unsteady solver.As for influence of discretization method,the second order scheme was used for eliminate the error due to numerical diffusion. The predicted axial velocity,temperature and humidity profile inside the spray drying chamber were found to be in fair agreement to the experimental data adopted from literature for all turbulence models tested in this work.A great potential of the Detached Eddy Simulation with unsteady conditions for predicting the flow pattern in a co-current spray dryer was uncovered as its provides more accurate predictions compared to the other models tested in this work.CFD analysis was also performed for the tall and short pilot scale spray dryer.The CFD analysis shows that the residence time for particles inside the tall chamber is much longer than those of shorter drying chamber due to intensive recirculation.Further analysis on the CFD results also uncovered a longer residence time for smaller particles as they tend to move around with the air flow and hence resulting in poor product quality.CFD may be used to further optimise the hydrodynamics in the spray dryer and hence improving product quality.Furthermore,results from this simulation may be useful for development of a more comprehensive and accurate model for counter current spray dryer in the future.